Determining the Prevalence of Hepatitis B, Hepatitis C and Other Opportunistic Co-Infection in HIV Infected Patients in a Tertiary Care Hospital of North India - Garg, Shikha (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
Background and Objectives: There is little data on the prevalence and demographics of co-infection with hepatitis B virus (HBV) and hepatitis C virus (HCV) in HIV-infected individuals, which results in increased hepatic complications and increased morbidity and mortality. Aim: This study was done to evaluate the prevalence of HBV and HCV in HIV infected individuals attending a tertiary care hospital of north India. Methods: A total of 104 cases with HIV infection were included in this retrospective study of 6 months duration (January to June 2019). Samples were tested for hepatitis B surface antigen (HBsAg) and anti-HCV antibodies by rapid detection method and/or enzyme linked immunosorbent assay (ELISA) method. HBsAg positive serum samples and Anti HCV positive samples were further tested for HBV DNA and HCV-RNA respectively. Other opportunistic infections were studied along with it. This study had been approved by Institutional Ethics committee. Results: Among the 104 HIV positive patients studied, 11(10.6%) were anti-HCV positive, 7 out of 11 (63.6%) of these sera were positive for HCV-RNA. Three(2.8%) suffered from chronic HBV co-infection (HBsAg positive), 2 out of 3 (66.7%) sera were positive for HBV-DNA. Triple infection with HBV, HCV and HIV was seen in 1 patient (0.9%) only. The most common mode of transmission was sexual promiscuity (76%), followed by infected needle/unknown (13.5%) and history of I/V drug abuse (10.5%). Demographic distribution shows maximum patients (38.5%) belonging to Ludhiana district followed by Hoshiarpur district of Punjab. Interpretation and conclusions: The findings of our study showed prevalence of 10.6% and 2.8% for Hepatitis C (anti HCV) and B (HBsAg) respectively in HIV positive patients. Co-infection with HBV and HCV is a common problem in HIV infected patients in India. HCV-HIV coinfection is more frequent than HBV-HIV co-infection overall .Hence, all HIV patients need to be routinely tested for markers of Hepatitis B and C.